2020
DOI: 10.3390/ijerph17124547
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effects of Marital Intimacy and Work Satisfaction in the Relationship between Husbands’ Domestic Labor and Depressive Mood of Married Working Women

Abstract: The purpose of the study was to examine the relationships between the husbands’ domestic labor and marital intimacy, work satisfaction, and depressive mood in married working women. We used the sixth (2016) dataset from the Women and Families Panel Survey conducted by the Korean Women’s Development Institute (KWDI). The subjects were 791 married working women who lived with a wage-earner husband and who did not have a housework assistant. The correlations between variables were measured and the fit of the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Suami pekerja rumah tangga, dalam suatu penelitian di Korea Selatan, didapatkan merupakan mediator terjadinya depresi pada istri melalui dampaknya pada keintiman pernikahan (Choi et al, 2020). Penelitian pada 154 pasien muda dengan kanker payudara, didapatkan bahwa kualitas hidup sub skala kesejahteraan fisik, kesejahteraan sosial, dan kesejahteraan fungsional berkorelasi secara signifikan dengan keintiman pernikahan.…”
Section: Hasil Dan Pembahasanunclassified
“…Suami pekerja rumah tangga, dalam suatu penelitian di Korea Selatan, didapatkan merupakan mediator terjadinya depresi pada istri melalui dampaknya pada keintiman pernikahan (Choi et al, 2020). Penelitian pada 154 pasien muda dengan kanker payudara, didapatkan bahwa kualitas hidup sub skala kesejahteraan fisik, kesejahteraan sosial, dan kesejahteraan fungsional berkorelasi secara signifikan dengan keintiman pernikahan.…”
Section: Hasil Dan Pembahasanunclassified
“…Gender discrimination climate in the workplace was also related to depression among married working women ( Batool, 2020 ; Choi et al, 2020 ; Kim et al, 2020a , 2020b ; Pavalko et al, 2003 ). According to a longitudinal study that explored at the relationship between workplace discrimination and women's physical and emotional health, women who perceived workplace discrimination had a high degree of psychological distress ( Pavalko et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the studies marriage satisfaction based on the intimacy between husband and wife could influence depression among married women employees ( Yuan et al, 2022 ; Wang & Peng, 2017 ). The studies on the negative effect of gender discrimination in the workplace on the level of depression among married women employees include those by Batool (2020) and Choi et al (2020) . Therefore, it can be assumed that the depression of married working women is related to work–family conflict, and this relationship can be regulated by marriage satisfaction and organizational gender discrimination climate.…”
Section: Introductionmentioning
confidence: 99%
“…Intimacy is the degree of closeness and support that each of the spouses feels and expresses. A person who experiences a higher level of intimacy can present themselves more desirably in a relationship and express their needs more effectively to their partner or spouse [6]. Luo et al [7] indicated that today's couples experience pervasive and severe problems in establishing and maintaining intimate relationships, while intimacy between spouses is one of the main keys to a successful and long-lasting marriage and its absence can cause marital failure.…”
Section: Introductionmentioning
confidence: 99%